PENILAIAN PROYEK DALAM PEMBELAJARAN MENULIS TEKS NARASI SIWA KELAS VII SMP NEGERI 18 JAMBI - Cristina Juniarti Hutabarat; Eddy Pahar Harahap; Akhyaruddin Akhyaruddin (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the implementation of project assessment in narrative text learning for grade VII students at SMP Negeri 18 Jambi City in the 2022/2023 academic year. This research uses a descriptive approach with a qualitative research type. The research data are student learning outcomes in writing narrative texts. Data sources were obtained from teachers and students at SMP Negeri 18 Jambi. Data collection techniques include observation, interviews, and documentation techniques. The results of the research on the implementation of project assessment in the learning process of writing narrative texts have been running in accordance with the steps of finding ideas, extracting ideas from reading, creating a series of stories, and developing narrative stories. The results of the project assessment received a very good score of 9 out of 25 students, or 36%, while those who received a good score were 16 out of 25 students, or 64%.